Awareness of students towards accountancy as a profession / Mohamad Azmi Nias Ahmad - Nias Ahmad, Mohamad Azmi (2003)
This study was taken to investigate the MRSM student's awareness towards accountancy as a Profession. The objectives of the study are to identify factors that attract the students in choosing Principle of Accounts subject for SPM examination and to examine the student's awareness towards accountancy as a profession. Overall, the findings show that MRSM students have a low level of awareness towards accountancy as a profession. The findings may have important implications for the profession'sfuture recruitment